The increasing role of the allergist in the management of infusion reactions at the Oncology Infusion Center - Borrás Cuartero, Julián; Torres Górriz, Maria Cruz; Stein Coronado, Cristina Isabel; Germán Sánchez, Adrián; Pesántez Méndez, Cristina Giovanna; Latorre Ibáñez, Maria Dolores; Enrique, Ernesto (Frontiers in Allergy, 2024)
BackgroundHypersensitivity reactions to chemotherapy disrupt treatment schedules and compromise patient outcomes. Rapid Drug Desensitization (RDD) enables patients to tolerate future treatments after an allergy workup. However, Same-Day Desensitization (SDD) is a novel approach that capitalizes on RDD to allow the continuation of chemotherapy on the same day as the index reaction, preventing treatment delays.ObjectiveTo evaluate the safety and efficacy of SDD in managing hypersensitivity reactions during chemotherapy and emphasize the essential role of allergists in the Oncology Infusion Center (OIC) for accurate drugs hypersensitivity reactions (DHRs) phenotyping and management.MethodsThis retrospective cohort included patients experiencing DHRs during chemotherapy. Under allergist supervision, SDD was performed once the index reaction was controlled. At a later date, clinical phenotypes and endotypes of DHRs were assessed through clinical history, skin tests, serum biomarkers (including tryptase and IL-6 levels), and drug provocation testing (DPT) to reach an accurate diagnosis.ResultsSDD was successful in 35 cases, even for patients with severe initial reactions. Only 14% experienced breakthrough reactions, all mild. Same-day assessment by allergists ensured a 92% correlation between initial and final diagnoses, optimizing DHR management. Early engagement with Allergy allowed 86% of reactive patients to continue treatment through RDD or after ruling out an allergy.ConclusionSDD is a safe and effective procedure that ensures that patients don't miss their oncology treatment on the day of a reaction. The presence of an allergist in the OIC is crucial for rapid access to accurate DHR phenotyping and optimal management, supporting personalized precision medicine in oncology.